Can the Poor Benefit from the Doha Agenda? The Case of Indonesia - Douglas H. Brooks; Guntur Sugiyarto (Asian Development Bank (ADB), 2005)
Agricultural trade barriers remain prevalent among developing countries. Three important questions arise from this fact. First, is there any justifiable reason for agricultural protection in developing countries? Second, what are the effects of farm trade liberalization that might result from the Doha Development Agenda (DDA) in the current round of multilateral negotiations under the World Trade Organization? Third, as most farm producers are poor, will the poor benefit from the DDA and, if so, how? A computable general equilibrium model of the Indonesian economy is employed to answer these questions for one country by assessing the economywide welfare and distributional implications of the DDA, first with respect to the agricultural sector, and then to broader trade liberalization. To put the current agricultural protection into context, the assessment includes the welfare cost of existing sectoral taxes, and of changes in those taxes. Several trade liberalization scenarios are introduced. These include a complete removal of tariffs on agricultural products, which is then combined with a complete removal of domestic taxation on agricultural products. A complete trade liberalization simulation is also included to provide a ceiling for the benefits from trade liberalization. The overall results suggest that a removal of agricultural tariffs alone will generate adverse effects, while its combination with removal of agricultural taxes will create benefits for the economy, households, and the poor. Single-sector trade liberalization seems not a good strategy and a more comprehensive trade reform is desirable. In addition, the last simulation result provides further evidence of the inefficiency of raising revenue through commodity taxation.
hdl:11540/1900
Keywords: 330; Agraraußenhandel; Handelsliberalisierung; WTO-Recht; Entwicklung; Tansania